Pengaruh Penggunaan Teknologi Informasi Terhadap Pelayanan Administrasi Sekolah di SLTA dan Madrasah - Sundari, Gita; Rusdinal; Sulastri; Yulianto Santoso (Journal of Practice Learning and Educational Development, 2024)
This research aims to obtain information about the use of information technology and school administrative services, as well as the impact of information technology use on school administrative services. The hypothesis proposed in this study is "there is a significant influence between the use of information technology and school administrative services in high schools and madrasas in Padang Panjang City." The population of this study consists of 110 school administrative staff, and a sample of 68 school administrative staff was taken using the Proportionate Stratified Random Sampling technique. Data were collected through a questionnaire that had been tested for validity and reliability. Data analysis used the Product Moment correlation technique with the help of SPSS version 29.0 in 2024. The research results show that: (a) the use of information technology is classified as good (80.30% of the ideal score), (b) the school administration services are classified as fairly good (77.84% of the ideal score), and (c) there is a significant relationship between the use of information technology and school administration services in high schools and madrasas in Padang Panjang City.